2002
DOI: 10.4319/lo.2002.47.5.1562
|View full text |Cite
|
Sign up to set email alerts
|

Does competition for nanomolar phosphate supply explain the predominance of the cyanobacterium Synechococcus?

Abstract: Abstract-Experimental work during a cruise along a W-E transect in the Mediterranean Sea suggests that (1) orthophosphate concentrations in the upper photic zone show a decreasing trend from the west to the east reaching levels well below 1 nM and (2) microorganisms in the 0.6-2-m size fraction, probably Synechococcus, have, in addition to high affinity for orthophosphate, significantly higher maximum uptake rates than heterotrophic bacteria or eukaryotic algae. These specific advantages concerning orthophosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
113
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(131 citation statements)
references
References 22 publications
16
113
2
Order By: Relevance
“…Yet it appears that not all marine cyanobacteria are equal in their ability to substitute SQDG for PG. For example, our lipid extracts from marine Synechococcus, which were grown at phosphate concentrations similar to Prochlorococcus cultures, show significantly lower SQDG͞PG (12 Ϯ 5 vs. 37 Ϯ 7), which is consistent with observations that Prochlorococcus are more tolerant of low-phosphorus conditions than Synechococcus (11,12).…”
Section: Significance Of Sulfolipids In Cyanobacteriasupporting
confidence: 76%
See 2 more Smart Citations
“…Yet it appears that not all marine cyanobacteria are equal in their ability to substitute SQDG for PG. For example, our lipid extracts from marine Synechococcus, which were grown at phosphate concentrations similar to Prochlorococcus cultures, show significantly lower SQDG͞PG (12 Ϯ 5 vs. 37 Ϯ 7), which is consistent with observations that Prochlorococcus are more tolerant of low-phosphorus conditions than Synechococcus (11,12).…”
Section: Significance Of Sulfolipids In Cyanobacteriasupporting
confidence: 76%
“…This result would be at odds with work suggesting that respiration outweighs photosynthesis in the open ocean (36) but could explain, at least to some degree, the conflicting trends of increasing inventories of organic carbon (7) and decreasing inventories of nutrient phosphorus in the NPSG (1,6). Indeed, Prochlorococcus is abundant in other oligotrophic environments where PO 4 3Ϫ is an order of magnitude less abundant than in NPSG (11). Yet it appears that not all marine cyanobacteria are equal in their ability to substitute SQDG for PG.…”
Section: Significance Of Sulfolipids In Cyanobacteriacontrasting
confidence: 54%
See 1 more Smart Citation
“…Recent studies have suggested phosphorus as the most limiting nutrient with regard to phytoplankton. As a rule, affinity constants for orthophosphate by Cyanobacteria occurred (Moutin et al, 2002;Tanaka et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The main challenge to making these measurements was to separate the response of Prochlorococcus in the NPSG from that of the more abundant (Campbell et al 1997;Bjö rkman et al 2000 consumption by these two groups (Moutin et al 2002). As an alternative, flow cytometry could be used to physically separate Prochlorococcus from heterotrophic bacteria (Zubkov et al 2003).…”
mentioning
confidence: 99%